Adjunctive pregabalin vs gabapentin for focal seizures: Interpretation of comparative outcomes. (20th September 2016) - French, Jacqueline; Glue, Paul; Friedman, Daniel; Almas, Mary; Yardi, Nandan; Knapp, Lloyd; Pitman, Verne; Posner, Holly B.
Abstract : Objective: To evaluate the comparative safety and adjunctive efficacy of pregabalin and gabapentin in reducing seizure frequency in patients with partial-onset seizures based on prestudy modeling showing superior efficacy for pregabalin. Methods: The design of this comparative efficacy and safety study of pregabalin and gabapentin as adjunctive treatment in adults with refractory partial-onset seizures was randomized, flexible dose, double blind, and parallel group. The study included a 6-week baseline and a 21-week treatment phase. The primary endpoint was the percentage change from baseline in 28-day seizure rate to the treatment phase. Results: A total of 484 patients were randomized to pregabalin (n = 242) or gabapentin (n = 242). Of these, 359 patients (187 pregabalin, 172 gabapentin) completed the treatment phase. The observed median and mean in percentage change from baseline was −58.65 and −47.7 (SD 48.3) for pregabalin and −57.43 and −45.28 (SD 60.6) for gabapentin. For the primary endpoint, there was no significant difference between treatments. The Hodges-Lehman estimated median difference was 0.0 (95% confidence interval −6.0 to 7.0). Safety profiles were comparable and consistent with prior trials. Conclusions: The absence of the anticipated efficacy difference based on modeling of prior, nearly identical trials and the larger-than-expected response rates of the 2 antiepileptic drugs were unexpected. These findings raise questions that are potentially important to consider in future comparative efficacy trials. ClinicalTrials.gov identifier : NCT00537940. Classification of evidence: This study provides Class II evidence that for patients with partial seizures enrolled in this study, pregabalin is not superior to gabapentin in reducing seizure frequency. Because of the atypical response rates, the results of this study are poorly generalizable to other epilepsy populations.